Digital digging on the Molyvoti, Thrace, Archaeological project: IDig and a new web application (Research Announcements "Heritage BG", 2024)
Twenty years ago, the idea of widespread technology integration in archaeological research was beyond imagination. The excavation in Molyvoti, a walled classical city situated along the coastal region ofAegean Thrace identified as Stryme, the Thasian emporion, exemplifies the transition from traditional to modern technological methodologies in archaeological studies. The excavation endeavors at Molyvoti, which trace their origins to the 1950s, serve as a compelling illustration of the shift towards incorporating advanced technologies for research purposes. References:Bakalakis, G. (1967). Anaskafi Strymes. Thessaloniki.IThrAeg = Loukopoulou, L., Zournatzi, A., Parissaki, M.-G., Psoma, S. (2005). Epigraphes tis Thrakis tou Aigeou metaxi ton potamon tou Nestou kai Evrou (Nomoi Xanthis, Rhodopis kai Evrou). Athens.Karadedos, G. (1990). Ysteroclasiko spiti sti Maroneia Thrakis. – Egnatia, No. 2, 265-314.Lavvas, G., Karadedos, G. (1990). Vitrouvianes efarmoges sto theatro kai se isteroclasiki katoikia tis Maroneias]. In: Mnimi D. Lazaridi, Polis kai Chora stin archaia Makedonia kai Thraki, Praktika archaiologikou synedriou stin Kavala 9-11 Maiou 1986. Thessaloniki, 655-672.Tasaklaki, M. (forthcoming B). I klasiki poli sti xersoneso tis Molyvotis. I nomismatiki martyria. In: I Komotini kai i perioxi tis apo tin arhaiotita eos tin egkatastasi ton prosfygon tis mikrasiatikis katastrofis, 1o triimero diethnes synedrio, Komotini, 6-8 Maiou 2022.Tasaklaki, M., Leou, Z. (forthcoming). ta tafika ethima kai praktikes apo tous arhaikous eos tous romaikous hronous mesa apo ta nekrotafeia tis Dikaias, tis polis sti Molyvoti kathos kai allon theseon tou dimou Komotinis. In: I Komotini kai i periohi tis apo tin arxaiotita eos tin egkatastasi ton prosfygon tis mikrasiatikis katastrofis, 1o triimero diethnes synedrio, Komotini, 6-8 Maiou 2022.Terzopoulou, D. (2004). ta enepigrafa mnimeia tis arhaias Strymes. - Archaeologikon Deltion, No 55, Meletes, 143-182.Triantaphyllos, D., Tasaklaki, M. (2012). I keramiki apo dyo archaica nekrotafia tis Aegeakis Thrakis. In: Archaic pottery of the Northern Aegean and its Periphery (700-480 BC) Proceedings of the Archaeological Meeting Thessaloniki, 19-22 May 2011 (eds. M. Tiverios, V. Misailidou-Despotidou, E. Manakidou, A. Arvanitaki). Thessaloniki, 475-488.Triantaphyllos, D., Tasaklaki, M. (forthcoming). Δίκαια παρ’ Άβδερα revisited. In: XI International Congress of Thracology, 8-12 November 2010, Istanbul (ed. M. Sayar).Triantaphyllos, D., Terzopoulou, D. (2012). Anaskafi Strymes(?). In: diinessa, timitikos tomos gia tin Katerina Romiopoulou. (eds. P. Adam-Veleni, K. Tzanavari). Thessaloniki, 141-156.Arrington, N. T., Terzopoulou, D., Tasaklaki, M., Hudson, N., Brellas, D., Bellas, G., Lawall, M., White, C., Baloukidis, D. (forthcoming). Molyvoti, Thrace, Archaeological Project: 2019 and 2022 Preliminary Report. – Hesperia.Arrington, N. T., Terzopoulou, D., Tasaklaki, M., Makris, G., Hudson, N. (2023). The Molyvoti, Thrace, Archaeological Project (MTAP): Discovering and Recording a Diachronic Landscape. In: Surveying Aegean Thrace in the Digital Era. Proceedings of the ArcGeoPerSa Workshop (HFRI-FM17-750) (eds. A. Avramidou – J. C. Donati). Komotini, 79-98.Arrington, N. T., Terzopoulou, D., Tasaklaki, M., Tartaron, T. (eds.) (forthcoming). A Trading Port in Aegean Thrace: The Molyvoti, Thrace, Archaeological Project (Ancient Stryme) 2013-2015, vol. I, Hesperia Supplement 54.Arrington, N. T., Terzopoulou, D., Tasaklaki, M., Weaverdyck, E. (2022). The Classical City on the Molyvoti Peninsula (Aegean Thrace): Landscape, Urban Development, and Economic Networks. In: The Riverlands of Aegean Thrace: Production, Consumption and Exploitation of the Natural and Cultural Landscape, XIXth ICCA, Archaeology and Economy in the Ancient World, 22-26 May 2018 (ed. E. Kefralidou). Cologne-Bonn, 373-394.Arrington, N. T., Terzopoulou, D., Tasaklaki, M. (forthcoming). Thrace: Houses at ancient Stryme. In: Routledge Handbook of Classical Houses and Households (ed. B. A. Ault).Arrington, N. T., Padgett, M. (2019). House, City, Country: Classical Fine Wares from the Molyvoti Peninsula (“Ancient Stryme”), Thrace. In: Classical Pottery of the Northern Aegean and its Periphery (480-323/300 B.C.), Proceedings of the International Archaeological Conference, Thessaloniki, May 17-20, 2017 (eds. E. Manakidou, A. Avramidou). Thessaloniki, 521-532.Arrington, N. T., Terzopoulou, D., Tasaklaki, M., Lawall, M., Brellas, D., White, C. (2016). Molyvoti, Thrace, Archaeological Project. 2013 Preliminary Report. – Hesperia, No. 85, 1-64.Baralis, A. (2008). The Chora Formation of the Greek Cities of Aegean Thrace. A Chronological Approach to the Colonization Process. In: Meetings of Cultures in the Black Sea Region: Between Conflict and Coexistence, Black Sea Studies 8 (eds. P. G. Bilde, J. H. Petersen). Aarhus, 101-130.Damyanov, M. (2015). The Greek Colonists. In: A Companion to Ancient Thrace (eds. J. Valeva, E. Nankov, D. Graninger). Maldet – Oxford, 295-307.Isaac, B. (1986). The Greek Settlements in Thrace until the Macedonian Conquest. Leiden.Karambinis, M. (2019). Urban Networks in Early Roman Macedonia and Aegean Thrace. In: Regional Urban Systems in the Roman World, 150 BCE – 250 CE, Mnemosyne Supplement 431 (eds. L. de Ligt, J. Bintliff). Leiden, 440-481.Loukopoulou, L. D., Psoma, S. (2008). Maroneia and Stryme Revisited: Some Problems of Historical Topography. In: Thrakika Zetemata I, ΜΕΛΕΤΗΜΑΤΑ 58 (eds. L. D. Loukopoulou, S. Psoma). Athиnes, 55-86.May, J. M. (1965). The Coinage of Dikaia-by-Abdera, c. 540/35-476/5 B.C. - Numismatic Chronicle, No. 5, 1-25.Psoma, S., Karadima, C., Terzopoulou, D. (in coll. with M. Tasaklaki) (2008). The Coins from Maroneia and the Classical City at Molyvoti. A Contribution to the History of Aegean Thrace, ΜΕΛΕΤΗΜΑΤΑ 62. Athens.Tasaklaki, M. (forthcoming A). Coins. In: A Trading Port in Aegean Thrace: The Molyvoti, Thrace, Archaeological Project (Ancient Stryme), 2013-2015 (eds. N. Arrington, D. Terzopoulou, M. Tasaklaki, T. T. Tartaron), Hesperia supplement 54.Tasaklaki, M. (forthcoming C). Aegean Thrace and the Ionian Material Koine. Imitations of the Ionian vases produced by local Workshops. In: Mimeseis Ionian cups Thrace between East and West, Mimesis, International colloquium on the Imitation in Ancient Thrace. In Memory of Prof. Olivier Picard (eds. A. R. Solas, I. Topalilov).Terzopoulou, D., Tasaklaki, M., Arrington, N. T. (2023). Stryme, A Thasian Polis on the Aegean Coast of Thrace. Space Organization and Domestic Architecture. In: The Ancient Greek City I: Domestic and Public Architecture in its Social and Political Context, Annual Meeting of the AIA, New Orleans, LA, January 6, 2023 (eds. A. G. Vlachopoulos, A. Gadolou). Athens, 17-32.Tiverios, M. (2008). Greek Colonisation of the Northern Aegean. In: Greek Colonisation: An Account of Greek Colonies and Other Settlements Overseas, ΙΙ. Mnemosyne Supplement 193 (ed. G. R. Tsetskhladze). Leiden – Boston, 1-154.Triantaphyllos, D. (2000). La nécropole de la colonie thasienne de Strymé. In: Pratique funéraire dans l’Europe des XIIe-IVe siucles av. J.-C., Actes du IIIe Colloque international d’Archéologie funéraire organize Tulcea, 15–20 septembre 1997. Tulcea, 87-104.
Keywords: Aegean Thrace; Stryme; databases; material registration